The comparative efficiency of aspiration equipment for dust protection of elevator complexes with a capacity of 20,000 tons - D. S. Efimov; O. E. Krotova; S. M. Chelbin; D. V. Rudoy; E. N. Ochirova; D. S. Mashtykov (Современная наука и инновации, 2023)
The purpose was to study the efficiency of the use of aspiration equipment of the BC type and its efficiency of use today in comparison with the advanced achievements of aspiration technology in the elevator industry for the process of creating air dilution and removing grain dust during the operation of equipment using the example of a modern silo elevator with a capacity of 20,000 tons, in grain production, including acceptance and storage of air-conditioned grains. In order to achieve the purpose of the study and answer the research questions about the effectiveness of the installations of battery cyclones of the BC type, a calculation was made on the amount of grain dust emitted for a period of 365 days of elevator operation in 3 shifts according to the "Temporary method of calculating planned indicators for the protection of atmospheric air of grain processing enterprises and elevators", in accordance with the "Calculation Method aspiration installations and explosion-discharge devices", series 14, issue 1 "Industrial safety of explosive grain storage and processing facilities". According to the results obtained, according to the calculation, the cleaning coefficient of battery installations was established, which amounted to 95-96%, the amount of grain dust removed during the year of operation of the elevator is 40.16 tons. This indicator has a positive effect on the evaluation of the efficiency of battery-operated aspiration units of the BBTS type. A number of disadvantages and advantages of BBC type aspiration units over modern aspiration equipment have been identified on the example of a point local filter. To date, battery installations of the BPC type are effective aspiration equipment, despite the undeniable advantages of innovative point local filters, the essential problem of which is their low versatility.